Osteopontin in Seminal Plasma and Sperm Membrane of Dogs - Souza, Fabiana Ferreira de [UNESP]; Chirinea, V. H. [UNESP]; Martins, M. I. M.; Lopes, Maria Denise [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
The objective of this work was to describe the presence of osteopontin (OPN) in canine seminal plasma and sperm membranes. A pool of seminal plasma and sperm membrane extract from 30 dogs was used. Polyacrylamide electrophoresis gels were performed and the bands were transferred to nitrocellulose paper and Western blot was undertaken using an antibody anti-OPN. Two and 12 bands were marked in the seminal plasma (77.2 and 15.6 kDa) and sperm membrane extracts (70.6-26.6 kDa), respectively. However, from 12 marked bands in the sperm membrane extract, only three (46.4, 37.7 and 36.5 kDa) were strongly marked. We conclude that, seminal plasma and sperm membranes from dogs contain different isoforms of OPN; yet, further studies will be necessary to determine their function in this species.